2006
DOI: 10.1002/ijc.22070
|View full text |Cite
|
Sign up to set email alerts
|

Reduced incidence of cervical cancer in mothers of sons with allergic rhinoconjunctivitis, asthma or eczema

Abstract: Because infection with human papillomavirus is a necessary cause of cervical cancer, it is likely that host immunological factors involved in defense against such infections are important for susceptibility to this cancer. By examining associations between allergy in sons and cervical cancer in their mothers, we aimed to test for genetic components involved in both allergy and cervical cancer development. Women born in Sweden between 1932 and 1960 with at least 1 son with medical records from military conscrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The association was also particularly strong for squamous cell carcinoma of the esophagus, a cancer for which data regarding involvement of HPV has been disputed (57)(58)(59). Interestingly, the same common genetic polymorphisms may predispose to both allergies and cervical cancer, and a reduced incidence of cervical cancer has been reported in women whose sons have allergic conditions (60,61). These reports suggest a genetic component common to allergies and cervical cancer.…”
Section: Discussionmentioning
confidence: 93%
“…The association was also particularly strong for squamous cell carcinoma of the esophagus, a cancer for which data regarding involvement of HPV has been disputed (57)(58)(59). Interestingly, the same common genetic polymorphisms may predispose to both allergies and cervical cancer, and a reduced incidence of cervical cancer has been reported in women whose sons have allergic conditions (60,61). These reports suggest a genetic component common to allergies and cervical cancer.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have shown that eczema is associated with a reduced risk of various malignances (e.g. skin, lung, and cervical) [ 17 , 37 , 38 ]. However, the relationship between eczema and risk of glioma has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma and allergy have previously been inversely correlated with the risk of cervical cancer. 17,26 The next strongest pathway was that of Folate biosynthesis, where the associations detected were mainly related to the tissue nonspecific alkaline phosphatase (ALPL) gene. Mutations in this enzyme cause hypophospatasia; a metabolic bone disease characterized by defects in skeletal mineralization.…”
Section: Discussionmentioning
confidence: 99%